Knowledge, Attitudes, and Practices of School Snack Food Safety among Junior High School Students in Palu City - Dwi Rahmat Fadhilah; Talitha Syifa Hafidzah; Muhammad Akbar Ramadhan; Darrel Mathew Mamonto; Dewi Susetiyany Ichsan (Journal of Nutrition Explorations, 2026)
Adolescents frequently consume school snacks, which may pose health risks if safety standards are not maintained. This study aimed to assess the knowledge, attitudes, and practices (KAP) of students at SMP Negeri 1 Palu regarding school snack food safety. A descriptive-analytical design was conducted in August 2023 with 256 students from grades 7–9. Data were collected using a standardized KAP questionnaire provided by the Indonesian Food and Drug Monitoring Agency (BPOM RI) via Google Forms, administered under the supervision of trained PJAS cadres. Ethical approval was obtained from the Research Ethics Committee of Poltekkes Kemenkes Palu. Data were analyzed using SPSS 22.0 with univariate and bivariate methods. Results indicated that the majority of students demonstrated good knowledge (83.5%) about food registration, expiration dates, hygiene, and contamination risks. Positive attitudes toward safe food handling were observed in 89.8% of respondents, while safe practices, including avoidance of expired foods and contaminated packaging, were reported by 90% of students. However, occasional lapses were noted in utensil usage and purchasing from sick vendors. The findings highlight that students are generally aware of key food safety principles, but targeted educational interventions are needed to reinforce consistent safe practices. Implementing regular food safety education, canteen audits, and parental involvement may further enhance food safety compliance, contributing to improved adolescent health outcomes and safer school food environments